Age and sex differences in c-Fos expression and serum corticosterone concentration following LPS treatment. (1st October 2015) - Girard-Joyal, O.; Faragher, A.; Bradley, K.; Kane, L.; Hrycyk, L.; Ismail, N.
Highlights: Adult male and female mice treated with LPS display greater c-Fos expression than their saline-treated counterparts. Pubertal mice treated with LPS do not display higher levels of c-Fos expression than saline-treated controls. LPS increases corticosterone levels in pubertal and adult mice, but the highest increase is found in adult female mice. Abstract: Exposure to an immune challenge during peripuberty/adolescence, but not in adulthood, can cause enduring alterations in reproductive and non-reproductive behaviors. This suggests that the peripubertal/adolescent brain might respond differently to a stressor, like an immune challenge, than the adult brain. The goal of this study was to examine whether there are age and sex differences in the acute response to an immune challenge. To examine this research question, we investigated c-Fos expression in various brain regions. Corticosterone (CORT) concentration in the serum was quantified to examine hypothalamic–pituitary–adrenal axis (HPA-axis) responsiveness. Results showed that lipopolysaccharide (LPS; a bacterial endotoxin) treatment, induced a significant increase in the number of c-Fos immunoreactive cells in adult male and female mice compared to their saline controls. However, in peripubertal/adolescent mice, LPS treatment failed to increase the number of c-Fos immunoreactive cells in both male and female mice compared to their saline controls. LPS treatment also significantly increased serum CORT concentration in all mice regardless of sex and age. However, adult female mice treated with LPS showed significantly greater serum CORT concentration compared to adult and peripubertal/adolescent males and peripubertal/adolescent females treated with LPS. These findings support our hypothesis and suggest that there are important age and sex differences in acute immune response, which may allude to mechanisms for the enduring behavioral alterations, observed previously in mice exposed to an immune challenge during puberty but not in adulthood.